If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 11 = 6x + -9 + 3 Reorder the terms: 11 + 9x = 6x + -9 + 3 Reorder the terms: 11 + 9x = -9 + 3 + 6x Combine like terms: -9 + 3 = -6 11 + 9x = -6 + 6x Solving 11 + 9x = -6 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 11 + 9x + -6x = -6 + 6x + -6x Combine like terms: 9x + -6x = 3x 11 + 3x = -6 + 6x + -6x Combine like terms: 6x + -6x = 0 11 + 3x = -6 + 0 11 + 3x = -6 Add '-11' to each side of the equation. 11 + -11 + 3x = -6 + -11 Combine like terms: 11 + -11 = 0 0 + 3x = -6 + -11 3x = -6 + -11 Combine like terms: -6 + -11 = -17 3x = -17 Divide each side by '3'. x = -5.666666667 Simplifying x = -5.666666667
| 3x-18=12+7x | | 4x-4x+5=12 | | 4+5(x-2)=6+7(x-2) | | (10-2x)(8-2x)(x)=f(x) | | -8+x=4x+1 | | cos+2sec=-3 | | -16=2(1-5x)+4 | | x+3.5=8.5-9x | | 10x-5(x-2)=30 | | 7-4x-3x-5=6x+1+2x-3 | | =(4x-3)(2x+7)-(4x-3)(6-x) | | 3(a+b)+2(a-b)= | | 0.1x+0.25x=20.65 | | -3=153 | | 2v-26=-9(v+9) | | 9x-10=2x+6 | | 6(2.5+3x)-13x=8x-24 | | 16n-6-9n=43-2n+5 | | -6(2-4n)+5=161 | | y(y+5)+2(y-3)= | | 5(3x-4)=32+2x | | 336=6(-6x+8) | | 34-3x=6x+7 | | 0.66x-10=0.5x-8 | | 12t=-123 | | 364=-5(8n-8)+4 | | 2f(x)=4x-2 | | 2x-b=3 | | 0.2=10 | | 4r-4+8=-16 | | 2(x-6)-4x=-14 | | 4+3b+1=8 |